KAJIAN TARIF ANGKUTAN KOTA TRAYEK 011 DI KOTA TASIKMALAYA - Judiantono, Tonny; S. Permana, Yoga; Z. Tamin, Ofyar (Jurnal Transportasi, 2009)
The identification of transportation cost structure could help public transportation managers to determine the minimum tariff that can provide the maximum service for peoples. The tariff should be acceptable by the users and still gives fair profit for the operators. This study investigated the public transport Rute number 011(Sub Terminal Pancasila â Pasirangin) in Tasikmalaya City, to find the ability and the willingness to of the users. It was found that the current fare of public transport for Kota Tasikmalaya is higher than the ability to pay of the users.Keywords: tariff, fare, public transportation, and ability to pay.